2016 XXI Symposium on Signal Processing, Images and Artificial Vision (STSIVA) 2016
DOI: 10.1109/stsiva.2016.7743355
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability analysis during a dehydration protocol on athletes

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Thirty-three studies were included in the quantitative synthesis (meta-analysis). Amongst them, 24 studies assessed HR during exercise [22][23][24][26][27][28][29]34,35,38,40,42,43,[45][46][47][48][50][51][52][54][55][56][57], 11 studies analyzed HRV recovery [28,[31][32][33][34]36,39,40,51,53,54] and 7 analyzed SBP and DBP throughout recovery [26,30,31,37,41,52,55]. The search process and selection step details are established in the PRISMA protocol flow diagram (Figure 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three studies were included in the quantitative synthesis (meta-analysis). Amongst them, 24 studies assessed HR during exercise [22][23][24][26][27][28][29]34,35,38,40,42,43,[45][46][47][48][50][51][52][54][55][56][57], 11 studies analyzed HRV recovery [28,[31][32][33][34]36,39,40,51,53,54] and 7 analyzed SBP and DBP throughout recovery [26,30,31,37,41,52,55]. The search process and selection step details are established in the PRISMA protocol flow diagram (Figure 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The majority of studies were concerned with maintaining tests completed at the same time of day to standardize circadian influences. Some studies described the specified time of day throughout the morning [29,34,39,[43][44][45] or afternoon [26,30,33,36,37,40,51,52,54,55].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…It has also been shown that an increase in LF/HF ratio through reduction in central blood volume are indicative of increased risk of bradycardic hypotension [15]. Accordingly, the LF/HF has practical value in monitoring and adjusting hydration status in athletes and soldiers [16,17].…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…While exercising in the heat, hyperthermia, and dehydration are the two major factors that influence heart rate (HR) and HRV and impair performance (Achten & Jeukendrup, 2003; Ebert et al, 2007; González‐Alonso et al, 1997; Hillman et al, 2011). Dehydration reduces parasympathetic activity and increases sympathetic activity after exercise in the heat which is reflected in various HRV parameters (Carter et al, 2005; Castro‐Sepulveda et al, 2014; Severeyn et al, 2016). Even if exercising in temperate environments, hydration status has been shown to impact the recovery of HRV measures (Vanderlei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%